2017
DOI: 10.1158/1078-0432.ccr-17-0647
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Facilitate Resistance to Anti-VEGF Therapy by Altered VEGFR Expression

Abstract: Purpose VEGF-targeted therapies have modest efficacy in cancer patients, but acquired resistance is common. The mechanisms underlying such resistance are poorly understood. Experimental design To evaluate the potential role of immune cells in the development of resistance to VEGF blockade, we first established a preclinical model of adaptive resistance to anti-VEGF therapy. Additional in vitro and in vivo studies were carried out to characterize the role of macrophages in such resistance. Results Using mur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 29 publications
1
71
0
Order By: Relevance
“…The comparison of resistant versus sensitive tumors to anti-VEGF therapy revealed a higher number of TAMs in the non-responders [66]. In the same line, anti-VEGF mAbs showed higher therapeutic efficacy and higher inhibition of vessel formation, upon depletion of TAMs with zoledronic acid, in several tumor models [67]. This effect was also observed in murine glioblastoma treated with vatalanib, a small protein kinase inhibitor that blocks angiogenesis.…”
Section: Interaction Of Tams With Anti-angiogenic Therapymentioning
confidence: 78%
“…The comparison of resistant versus sensitive tumors to anti-VEGF therapy revealed a higher number of TAMs in the non-responders [66]. In the same line, anti-VEGF mAbs showed higher therapeutic efficacy and higher inhibition of vessel formation, upon depletion of TAMs with zoledronic acid, in several tumor models [67]. This effect was also observed in murine glioblastoma treated with vatalanib, a small protein kinase inhibitor that blocks angiogenesis.…”
Section: Interaction Of Tams With Anti-angiogenic Therapymentioning
confidence: 78%
“…Anti-VEGF therapy, which was proven beneficial in ovarian cancer [20], is indeed known to modify the immune contexture [37] and is expected to reduce the amount of M2 macrophages. On the other hand, there is evidence that the presence of M2 macrophages can be an indication of resistance to anti-VEGF therapy [22,38,39]. It inhibits angiogenesis but can also promote the recruitment of TAM, immature monocytes, and other vascular modulators to the tumor site [39].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of VEGF stimulates both the migration of macrophages to the TME and their polarization toward a more M2 phenotype [17]. Furthermore, macrophages were shown to facilitate resistance to anti-VEGF treatment [22].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated TAM accumulation in the tumor mass after chemotherapy and antiangiogenic therapy. Thus, Dalton et al showed that recruitment of macrophages to the TME after anti-VEGF treatment leads to tumor growth as a mechanism of resistance to therapy but that depletion of macrophages inhibited tumor growth and improved the survival of tumor-bearing mice (49). The vascular disrupting agent combretastatin A4-P causes the increased production of CSF-1, CCL2, and CXCL12 that increases monocyte recruitment and TAM accumulation in tumor sites (50).…”
Section: Angiogenesismentioning
confidence: 99%
“…However, only a subset of patients respond efficiently to neoajuvant chemotherapy (NAC). Chemoresistance and chemotherapy-induced immunosuppression can result in the relapse of tumors and are critical for survival in cancer patients (49,104). Numerous studies have examined the molecular mechanisms that promote the chemoresistance of cancer cells, such as the induction of anti-apoptotic regulators, ABC transporters, aberrant transcription factor nuclear factor-κB (NF-κB) activity, and the mechanisms of damaged DNA repair (104)(105)(106).…”
Section: Chemotherapy Tams and Chitinase-like Proteinsmentioning
confidence: 99%